French People's positions on supervised injection facilities for drug users - Maria Teresa Munoz Sastre; Lonzozou Kpanake; Etienne Mullet (BMC, 2020)
Abstract Background Supervised injection facilities have been set-up in many countries to curb the health risks associated with unsafe injection practices. These facilities have, however, been met with vocal opposition, notably in France. As harm reduction policies can only succeed to the extent that people agree with them, this study mapped French people's opinions regarding the setting-up of these facilities. Method A sample of 318 adults--among them health professionals--were presented with 48 vignettes depicting plans to create a supervised injection facility in their town. Each vignette contained three pieces of information: (a) the type of substance that would be injected in the facility (amphetamines only, amphetamines and cocaine only, or amphetamines, cocaine and heroin), (b) the type of staff who would be working in the facility (physicians and nurses, specially trained former drug users, specially trained current drug users, or trained volunteers recruited by the municipality), and (c) the staff members' mission (to be present and observe only, technical counselling about safe injection, counselling about safe injection and hygiene, or counselling and encouragement to follow a detoxification program). Results Through cluster analysis, three qualitatively different positions were found: Not very acceptable (20%), Depends on staff and mission (49%), and Always acceptable (31%). These positions were associated with demographic characteristics--namely gender, age and political orientation. Conclusion French people's positions regarding supervised injection facilities were extremely diverse. One type of facility would, however, be accepted by a large majority of people: supervised injection facilities run by health professionals whose mission would be, in addition to technical and hygienic counselling, to encourage patrons to enter detoxification or rehabilitation programs.